2018
DOI: 10.14419/ijet.v7i2.3.12629
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support Rating System with Analytical Hierarchy Process Method

Abstract: Human resources within a company's organization are significant to support the progress and quality of the company in achieving the goal. However, to achieve it all of these employees must have other supporting factors such as endurance, diligence, and accuracy or other skills. These factors can manage a system that can help to make decisions. One of the methods that can be used for decision support system is by using AHP (Analytical Hierarchy Process) method, this method is chosen because it can select the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Particularly one of the stages of an association analysis called high frequent pattern mining captures the attention of many researchers to produce efficient algorithms. The importance of an associative rule can be identified by two parameters, support (the value of support) is the percentage of the combination of items in the database and confidence [15]- [18].…”
Section: Stage Associatementioning
confidence: 99%
“…Particularly one of the stages of an association analysis called high frequent pattern mining captures the attention of many researchers to produce efficient algorithms. The importance of an associative rule can be identified by two parameters, support (the value of support) is the percentage of the combination of items in the database and confidence [15]- [18].…”
Section: Stage Associatementioning
confidence: 99%
“…So the findings of the Norton Cybersecurity Insights Report (2015), which highlighted the bitter reality of crime online and personal effects on consumers in 17 countries [11]. This report found that globally, 62 percent of consumers believe that the credit card information they will be stolen online, and 38 percent of respondents think that they will lose the credit card information from their wallets.…”
Section: Impact On Consumer Confidencementioning
confidence: 99%
“…The term Internet define as the collection of millions of computers that provide a network of electronic connections between the computers [3]- [6]. The Internet has developed into an essential channel for product purchase and orientation [7]- [11]. It is not surprising if the development of the internet in countries such as the United States, the United Kingdom, Germany, and the Netherlands have made the internet as media or the favorite marketing channels [12]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Macroeconomic stability reflects a strong economic fundamentals position [1]- [3]. Economic stability and fundamentals interact and contribute closely to poverty [4].…”
Section: Introductionmentioning
confidence: 99%